Applying ultraviolet/persulfate (UV/PS) pre-oxidation for controlling ultrafiltration membrane fouling by natural organic matter (NOM) in surface water. (1st April 2018) - Tian, Jiayu; Wu, Cuiwei; Yu, Huarong; Gao, Shanshan; Li, Guibai; Cui, Fuyi; Qu, Fangshu
Abstract: Membrane fouling is a recognized obstacle for the application of ultrafiltration (UF) for drinking water treatment. In this study, ultraviolet/persulfate (UV/PS) oxidation was employed as a pretreatment to control membrane fouling caused by natural organic matter (NOM) in surface water. The effects of UV/PS pretreatment on amounts and characteristics of NOM were investigated in terms of dissolved organic carbon, fluorescent spectrum, molecular weight distribution and hydrophobicity. UF membrane fouling during filtration of raw and pre-oxidized water was compared with transmembrane pressure development, and the fouled membranes were further characterized using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The results indicate that NOM was considerably degraded and partially mineralized (∼58%) by UV/PS pretreatment at a PS dose not exceeding 0.6 mM and a UV irradiation time within 120 min, which was attributed to the generation of sulfate and hydroxyl radicals. The fluorescent compounds in NOM were almost completely degraded (>98%) by the UV/PS pretreatment at a PS dose of 0.4 mM, except for tyrosine-like proteins (∼80%). Moreover, UV/PS pretreatment decreased the ratio of macromolecular compounds and increased the hydrophilic fractions, resulting in reduced NOM adhesion to the membrane. Hence, irreversible fouling by NOM was significantly retarded (∼75%) by the UV/PS pretreatment due to reduction in NOM, and more importantly by preferential degradation of fluorescent, macromolecular and hydrophobic compounds. Fouling control performance was considerably improved at increased PS doses and extended UV irradiation time. Graphical abstract: Image 1 Highlights: UV/PS pre-oxidation was applied to retard UF membrane fouling by NOM. UV/PS substantially degraded and partially mineralized NOM (<58%) in surface water. Hydrophobic and fluorescent fractions of NOM were preferentially degraded by UV/PS. NOM fouling was notably retarded (∼75%) by UV/PS, particularly at higher doses. Fouling control was due to reduced NOM and improved characteristics.